Practicability of Blooms Mastery Learning Approach in Public Secondary Schools in Lagos Metropolis - Olusola Hassan; Olugbuyi Olushile; Adebajo Adefunke; Aleemi Saidat O (Pedagogi: Jurnal Ilmu Pendidikan, 2022)
The applicability of theories at times are occasioned by societal norms as it is a known fact that theorist are influenced by their immediate society. Hence, situation where most classes are overcrowded, one would begin to wonder if theory like Blooms mastery learning could be applicable Hence, this study investigated the applicability of mastery learning in public senior school as perceived by teachers. The study used descriptive survey research type. Two hundred and thirty teachers were sampled from public senior secondary schools in Kosofe local government area of Lagos. Teachers’ perception on the applicability of Mastery Learning (TPABML) was designed by the researcher to measure teachers perception, the instrument was validated with reliability index of 0.84. Data collected was analysed using mean score, percentages and independent t-test of significance. Findings showed that mastery leaning is not practicable in public senior secondary as perceived by teachers. The study also finds significant difference between teachers with post-graduate qualification and teachers with first degree, but no significant difference was found based on teachers experience. The study recommends that teachers should change their orientation and make efforts to apply mastery learning as it has recorded positive results when used. Keywords: Blooms mastery Learning, Perception, Practicability